PERANAN RUANG PADA RUMAH GADANG DI SUMATERA BARAT - Katherine Steffi Halim; Eveline C S (Jurnal Dimensi Seni Rupa dan Desain, 2009)
AbstractThe Role of Interior Space of Gadang House in west Sumatera. Indoensia is well known for its variety of culture. One of them is Minangkabau culture and it is a heredity heritage of the Minangbakau ancestor . One of this heritage is Rumah Gadang, which is a traditional house of the Minangkabau people . By knowing Rumah Gadang, the uniqueuness culture of Minangkabau is also known above all , Rumah Gadang is not just a place to live in for Minangkabau people , But also as a place for gathering of all the Minangkabau family. For the interior perspective , each divided base on different functuion according to the custom of there tadition. AbstrakPeranan Ruang Pada Rumah Gadang di Sumatera Barat. Indonesia terkenal terkenal akan keanekaragaman budayanya. Salah satuny adalah kebudaay ala Minangkabau. Kbudayaan ala Minang Kabau merupakan warisan turun temurun dari nenek moyang suku Minangkabau. Salah satu itu warisan itu adalah rumah gadang yang merupakan rumah masyarkat adat Minang Kabau. Mengenal rumah gadang berarti mengenal salah satu ke khasan mInangkabau apalagi Rumah Gadang tidang hanya sebagai tempat tinggal keluarga tetapi juga merupakan suatu lembaga di dalam keluarga besar Minang kabau. Dari segi interior Rumah Gadang memiliki ruang-ruang dengan fungsi masing-masing yang diatur dalam hukum adat.